2015
DOI: 10.4049/jimmunol.1400874
|View full text |Cite
|
Sign up to set email alerts
|

RelB/p50 Complexes Regulate Cytokine-Induced YKL-40 Expression

Abstract: The secreted protein, YKL-40, has been proposed as a biomarker of a variety of human diseases characterized by ongoing inflammation, including chronic neurological pathologies such as multiple sclerosis (MS)2 and Alzheimer’s disease. However, inflammatory mediators and the molecular mechanism responsible for enhanced expression of YKL-40 remained elusive. Using several mouse models of inflammation, we now show that YKL-40 expression correlated with increased expression of both IL-1 and IL-6. Furthermore, IL-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 63 publications
3
50
0
Order By: Relevance
“…We observed that YKL40 CSF levels correlate significantly with CSF cytokines such as IL1β, IL6 and osteopontin during the development of SIV encephalitis. Increases in these inflammatory mediators and others such as TNFα and C-reactive protein have been shown to correlate with CSF and CNS tissue YKL40 expression in other CNS inflammation models (Bonneh-Barkay et al, 2010b; Bhardwaj et al, 2015). The proinflammatory cytokines IL1β, IL6, oncostatin M, TNFα, and factors released from differentiating monocyte-derived macrophages have been shown to induce YKL40 expression in astrocytes (Singh et al, 2011; Bonneh-Barkay et al, 2012; Bhardwaj et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We observed that YKL40 CSF levels correlate significantly with CSF cytokines such as IL1β, IL6 and osteopontin during the development of SIV encephalitis. Increases in these inflammatory mediators and others such as TNFα and C-reactive protein have been shown to correlate with CSF and CNS tissue YKL40 expression in other CNS inflammation models (Bonneh-Barkay et al, 2010b; Bhardwaj et al, 2015). The proinflammatory cytokines IL1β, IL6, oncostatin M, TNFα, and factors released from differentiating monocyte-derived macrophages have been shown to induce YKL40 expression in astrocytes (Singh et al, 2011; Bonneh-Barkay et al, 2012; Bhardwaj et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Increases in these inflammatory mediators and others such as TNFα and C-reactive protein have been shown to correlate with CSF and CNS tissue YKL40 expression in other CNS inflammation models (Bonneh-Barkay et al, 2010b; Bhardwaj et al, 2015). The proinflammatory cytokines IL1β, IL6, oncostatin M, TNFα, and factors released from differentiating monocyte-derived macrophages have been shown to induce YKL40 expression in astrocytes (Singh et al, 2011; Bonneh-Barkay et al, 2012; Bhardwaj et al, 2015). In the CNS, YKL40 induction is mostly restricted to astrocytes (Bonneh-Barkay et al, 2010a; Craig-Schapiro et al, 2010; Bonneh-Barkay et al, 2012) and is regulated by STAT3 and RelB/p50 complexes of NF-κB (Bhardwaj et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…[94]. Significant expression differences of SERPINA1 (AAT) were identified as potential disease signatures for MS patients [95] and elevates in the cerebrospinal fluid of patients with MS [96]. CXCL16 could be a novel biomarker and potential predictor of disease activity in MS [97].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this time, and despite the wealth of studies being reported, how YKL-40 expression might be regulated by local and systemic factors has received scant attention. Indeed this was raised recently by Bhardwaj and co-workers [37] wherein the authors state: "Despite the numerous reports documenting elevated expression of YKL-40, relatively little is known about the inflammatory mediators and specific molecular mechanisms that control its expression. "…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence supporting an important role of STAT3 in YKL-40 expression in the context of IL-1, IL-6 and oncostatin M-stimulated human and murine astrocytes [37,54]. We therefore set out to investigate …”
Section: Discussionmentioning
confidence: 99%